ANALISIS FRAUD HEXAGON TERHADAP FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN SEKTOR INFRASTRUKTUR, UTILITAS DAN TRANSPORTASI - Herlina Nadziliyah; Niken Savitri Primasari (Accounting and Finance Studies, 2022)
Financial statement fraud is a discrepancy between the application of accounting principles and the preparation of financial statements with the aim of deceiving and deceiving users of financial statements. The approach taken to identify the factors that influence financial statement fraud, one of which is the fraud hexagon model. There are six factors in the fraud hexagon, namely Stimulus which will be represented by financial targets, Ability will be represented by a change of director, Collusion will be represented by political connections, Opportunity will be represented by the quality of external auditors, Rationalization will be represented by audit opinion and Ego is represented by many photos CEO. This study aims to analyze the effect of the fraud hexagon on fraudulent financial statements in infrastructure, utility and transportation sector companies listed on the Indonesia Stock Exchange in 2015-2019. Detection of the possibility of fraudulent financial statements is measured by the F-Score model. This study uses a purposive sampling technique with a sample of 25 companies and 125 data on annual reports and financial statements. The results showed that financial targets, the quality of external auditors, and the number of CEO photos had no effect on financial statement fraud, while the change of directors had a negative and significant effect on financial statement fraud, political connections had a positive and significant effect on financial statement fraud. Audit opinion has a negative and significant effect on financial statement fraud.